Relations and operations on predicates in the theory of intelligence - Khudhair, Abed Thamer (NTU "KhPI", 2017)
The purpose of the paper is to develop a formal technique of the theory of intelligence, namely, to develop the model and axiomatics in the language of algebra of finite predicates (AFP); to introduce a system of operations on relations; to construct of the algebra of relations. The methods of algebra of finite predicates, Boolean algebra and axiomatic method are used in the paper. In the paper the mathematical apparatus of the theory of intellect was further developed. The models and axiomatics of relations in the language of algebra of finite predicates (AFP) are developed, operations on relations such as the injection, equivalence, surjection, quasi-order, partial order, circulation and product of the relation are introduced. The algebra of relations is constructed. The system of operations on p redicates in the algebra of finite predicates, namely, the Boolean negation, disjunction, conjunction, implication, equivalence is axiomatically assigned. The basic predicates (predicates of object recognition) are introduced. The predicates of different orders correspond to concepts of a different level of abstraction. The solution of the AFP equations can be interpreted as a creative activity of a person. Due to the presence of such a wide and meaningful interpretation, even the purely mathematical development of the AFP allows at the same time to impel the development of the theory of intelligence. The minimization, decomposition, solution of equations, identical transformation of formulas are important tasks of the theory of intelligence.

Метою статті є розробка формальної методики теорії інтелекту, а саме розробка моделі і аксіоматики на мові алгебри кінцевих предикатів. Пропонується ввести систему операцій за відносинами для побудови алгебри відносин. У статті використані методи алгебри кінцевих предикатів, булева алгебра і аксіоматичний метод. У статті був розвинений математичний апарат теорії інтелекту. Розроблено моделі та аксіоматику відносин на мові алгебри кінцевих предикатів, введені операції над такими відносинами, як ін'єкція, еквівалентність, сюр'єкція, квазіпорядок, частковий порядок, циркуляція і добуток відносини. Побудована алгебра відносин. Аксіоматично призначається система операцій над предикатами в алгебрі скінченних предикатів, а саме: булеве заперечення, диз'юнкція, кон'юнкція, імплікація, еквівалентність. Вводяться основні предикати (предикати розпізнавання об'єктів). Предикати різних порядків відповідають поняттям іншого рівня абстракції. Рішення рівнянь алгебри кінцевих предикатівможна інтерпретувати як творчу діяльність людини. Через наявність такої широкої і змістовної інтерпретації навіть чисто математичний розвиток алгебри кінцевих предикатівдозволяє в той же час стимулювати розвиток теорії інтелекту. Мінімізація, декомпозиція, рішення рівнянь, тотожне перетворення формул є важливими завданнями теорії інтелекту.
Відношення і операції над предикатами в теорії інтелекту
Keywords: theory of intelligence; algebra of finite predicates; comparator identification; теорія інтелекту; алгебра скінченних предикатів; компараторна ідентифікація